In-situ synthesis of direct solid-state dual Z-scheme WO3/g-C3N4/Bi2O3 photocatalyst for the degradation of refractory pollutant - Jiang, Longbo (2020)
Artificial Z-scheme photocatalyst can not only reduce the recombination of photogeneraged electron–holepairs, but also retain prominent redox ability. In this study, direct solid-state dual Z-scheme WO3/g-C3N4/Bi2O3 photocatalyst was successfully synthesized by one step co-calcination stratage using tungstic acid, melamine and bismuth (III) nitrate pentahydrate as the precursors. Surface, morphological, and structural properties of the resulting materials were comprehensive characterized by XRD, XPS, SEM, TEM, UV–vis diffuse reflection spectroscopy, BET surface areas, photoluminescence and ESR analysis. The WO3/g-C3N4/Bi2O3 composite exhibited superior photocatalytic activities for tetracycline degradation than that of pure g-C3N4, WO3, Bi2O3 and their binary composites under visible light irradiation. The enhanced photocatalytic performance of WO3/g-C3N4/Bi2O3 composite can be ascribed to improved visible light absorption, increased surface area and enhanced separation efficiency of photo-generated electron-hole pairs. In addition, the photocatalyst exhibits high stability and reusability. On the basis of the results, a novel direct solid-state dual Z-scheme photocatalytic mechanism was also proposed.